A Futures Study of the Challenges and Drivers of Population Aging in Iran Using the Scenario Analysis Technique - Nasibeh Zanjari; Seyedeh Zahra Kalantari Banadaki; Rasoul Sadeghi; Ahmad Delbari (University of Social Welfare & Rehabilitation Sciences, 2024)
Objectives The rate of population aging in Iran is higher than the regional and global levels and Iran will enter the aging phase by 2040s. Considering the importance of the changes that population aging will create in Iranian society, this study aims to investigate the challenges and drivers of population aging in the next three decades in Iran. Methods & Materials The is a futures study using the scenario analysis method. Data were collected from different sources to understand the possible challenges of the population aging. Then, the obtained information was analyzed based on experts' opinions, structural analysis, cross-impact balance analysis, and scenario development. The data were analyzed using Mic-Mac and Scenario Wizard applications. Results The main drivers of population aging in the future will be governance variables in the field of old age, pension funds, health costs at micro and macro levels, distribution of welfare, fertility and household size, insurance coverage & pension. These variables will affect the geriatric workforce, intergenerational relationships, social participation, and the lifestyle and quality of life of older adults (outcomes). The possible scenarios for the future of population aging in 2050 were "Risky ageing", " Twilight ageing", "Dawn of ageing", and "Prosperous ageing".  Conclusion To achieve the desired scenario, i.e., " prosperous ageing" in Iran, we need a smart governance with a forward-looking view in the field of aging, equal welfare distribution, win-win pension funds, active economic and social participation of older adults, and fertility rate above the replacement level.